The Association between Anthropometric Variables, Functional Movement Screen Scores and 100 m Freestyle Swimming Performance in Youth Swimmers - Daisy Bond; Laura Goodson; Samuel W. Oxford; Alan M. Nevill; Michael J. Duncan (MDPI AG, 2015)
This study examined the association between anthropometric variables, Functional Movement Screen (FMS) scores and 100 m freestyle swimming performance in early adolescent swimmers. Fifty competitive, national level, youth swimmers (21 males, 29 females, mean age ± SD = 13.5 ± 1.5 years, age range 11-16 years) performed an "all-out" 100 m freestyle (front crawl) swim as fast as they could in a 50 m pool. A median divide for 100 m timed swim was also used to divide the sample into faster or slower groups. Height, body mass, skinfolds and limb lengths were also assessed. Maturation was calculated by proxy using anthropometric measures and participants also undertook the FMS as a measure of functional performance. Backwards linear regression indicated a significant model (p = 0.0001, Adjusted R2 = 0.638) explaining 63.8% of the variance in swim performance with total sum of skinfolds, upper leg length, lower leg length, hand length and total height significantly contributing to the model. Swimmers who were classed as fast had lower total sum of skinfolds (p = 0.005) and higher total FMS score (p = 0.005) compared to their slower peers. In summary, this study indicates that anthropometric variables significantly explained the variance in 100 m freestyle swimming performance in youth swimmers.